The Contribution of Endomycorrhiza to the Performance of Potato Virus Y-Infected Solanaceous Plants: Disease Alleviation or Exacerbation? - Deja-Sikora, Edyta; Mercy, Louis; Baum, Christel; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2019)
Solanaceae, comprising meaningful crops (as potato, tomato, pepper, eggplant and tobacco), can benefit from a symbiosis with arbuscular mycorrhizal fungi (AMF), which improve plant fitness and support plant defense against pathogens. Currently, those crops are likely the most impacted by Potato virus Y (PVY). Unfortunately, the effects of AM symbiosis on the severity of disease induced by PVY in solanaceous crops remain uncertain, partly because the interplay between AMF and PVY is poorly characterized. To shed some light on this issue, available studies on interactions in tripartite association between the host plant, its fungal colonizer and viral pathogen were analyzed and discussed. Although the best documented PVY transmission pathway is aphid-dependent, PVY infections are also observed in the absence of insect vector. We hypothesize the existence of an additional pathway for virus transmission involving AMF, in which the common mycorrhizal network (CMN) may act as a potential bridge. Therefore, we reviewed (i) the significance of AM colonization for the course of disease, (ii) the potential of AMF networks to act as vectors for PVY and (iii) the consequences for crop breeding and production of AM biofertilizers.